Tech strain: the musculoskeletal impact of electronic devices on young adults- a cross-sectional study - Mehmood, Mehwish; Rashid Khan, Shabnam; Aiesha Ishaque; Tariq, Rabbia; Himani, Gulshan (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the prevalence of upper extremity musculoskeletal disorders among young adults using handheld devices. Method: The cross-sectional study was conducted from September 2022 to March 2023 at the Indus Hospital and Health Network, Karachi, and comprised young adults of either gender aged 18-25 years studying in the affiliated colleges of nursing, biomedicine and physiotherapy. Data was collected using the online RedCap questionnaire. Data was analysed using SPSS 26. Results: Of the 412 participants, 242(58.7%) were females. The overall median age was 21 years (interquartile range: 20-23 years). A total of 280(68%) subjects had experienced upper musculoskeletal pain, and it was significantly associated with the frequency of using handheld devices (p=0.026), gender (p=0.001), frequently used hand (p=0.039) and purpose of mobile use (p=0.033). Conclusion: Duration of cell phone or hand-held device usage caused symptoms of musculoskeletal disorders. Key Word: Musculoskeletal impact, Handheld device use, Ergonomics, Young adults.